Characterization of pulse operation in depressed-cladding erbium doped fiber laser / Nur Sabirah Azhari - Nur Sabirah Azhari, Azhari (2016)
There has been intense work on the pulse operation in the conventional (C-) band, long wavelength (L-) band as well as in the 2 μm region. Nevertheless, as increasing demands for bandwidth have now pushed the envelope into the short-wavelength (S-band) region, it is of interest to further expand this coverage into the S-band region. In this research, depressed-cladding erbium doped fiber (DC-EDF) are chosen to accomplish S-band fiber laser because of their ability to provide and maintain high level of inversion along the fiber. It is designed with different index profile and this is called W-shape index profile. The system uses a 15 m long DC- EDF as a gain medium which is spooled with a diameter of about 9cm so as to inhibit operation at wavelengths of more than 1530 nm, while a thin CNT film is sandwiched between two connectors to function as the SA for the generation of the desired Q-switched pulses. To investigate the tunable Q-Switched fiber laser operating in the S-band region, a tunable Fabry-Perot etalon filter is inserted in the setup as the wavelength tuning and filtering mechanism. The tuning range of the laser output carrying the Q-switching pulses covers a wide wavelength range of 47 nm, which spans from 1479 nm to 1526 nm. In this research, we investigate and demonstrate the pulse operation in DC-EDF. To the best of our knowledge, this is the first demonstration of characterization pulse operation in S band region using DC-EDF.